Operations research and enterprise systems : 8th International Conference, ICORES 2019, Prague, Czech Republic, February 19-21, 2019, Revised selected papers /: 8th International Conference, ICORES 2019, Prague, Czech Republic, February 19-21, 2019, Revised selected papers. (2020) - Unknown
No abstract available